2022
DOI: 10.1097/md.0000000000030569
|View full text |Cite
|
Sign up to set email alerts
|

Effects of high-quality nursing care on quality of life, survival, and recurrence in patients with advanced nonsmall cell lung cancer

Abstract: Background: Postoperative nursing can improve the quality of life (QoL) and functional prognosis for lung cancer patients. The purpose of this study was to evaluate the effects of high-quality nursing on inflammation and prognosis in postoperative patients with advanced nonsmall cell lung cancer (NSCLC). Methods: A total of 372 patients with NSCLC were enrolled between the May 2014 and June 2016. Patients were randomly received high-quality nursing (n = 192) or normal nursi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 21 publications
0
4
0
Order By: Relevance
“…QoL is one of the crucial indices to evaluate the disease condition and therapeutic effect of LC patients [11]. The diagnosis and treatment of LC may compromise the physical and psychological health of patients, lowering their QoL [36].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…QoL is one of the crucial indices to evaluate the disease condition and therapeutic effect of LC patients [11]. The diagnosis and treatment of LC may compromise the physical and psychological health of patients, lowering their QoL [36].…”
Section: Discussionmentioning
confidence: 99%
“…In addition to suffering from symptoms associated with LC, such as pain, chemotherapy reactions, and sleep difficulties, LC patients also endure a Am J Cancer Res 2024;14(3):1278-1291 range of psychological and emotional distress, including anxiety, depression, despair, a sense of burden, and concerns about their families. These factors compromise both their physical and mental health, as well as their dignity and quality of life (QoL) [10,11]. Prior research has revealed that LC patients have a high demand for continuous care after operation, mainly involving environmental support, self-health management knowledge and skills, health improvement, and psychological support [12].…”
Section: Introductionmentioning
confidence: 99%
“…Answer patients' concerns and prevent patients from infection appropriately. Give patients appropriate dietary care and instruct them to have a reasonable diet and balanced nutrition[ 18 ].…”
Section: Methodsmentioning
confidence: 99%
“… 9 Therefore, in order to effectively alleviate the pain of burn patients and significantly improve the symptoms of anxiety and depression, quality nursing services can be implemented for patients. It has been proven that the implementation of quality care can reduce the intensity of postoperative pain and adverse reactions in cardiac surgery patients and promote recovery 10 ; it can reduce postoperative anxiety, depressive symptoms and psychological stress in patients with advanced non‐small cell lung cancer 11 ; it also improves the negative mood and quality of life of women with gestational hypertension and increases satisfaction with care. 12 Several scholars have explored the clinical application effect of quality nursing interventions in burn patients, and this study aims to explore the effect of implementing quality nursing interventions on wound pain and adverse emotions in burn patients via meta‐analysis and then provide evidence‐based medicine for the clinical practice of quality nursing.…”
Section: Introductionmentioning
confidence: 99%